Sand Granules Ekstrak Biji Alpukat (Persea Americana Seed Extract) sebagai Larvasida Alami Pemberantas Demam Berdarah Dengue : Sand Granules of Avocado Seed Extract (Persea Americana Seed Extract) as Natural Larvaside of Dengue Fever - Rukminingsih, Fef; Pujiastuti, Anasthasia (Universitas Tadulako, 2020)
Dengue hemorrhagic fever (DHF) threatens people in the rainy season. DHF is one of the major public health problems in Indonesia. These problems encourage an effort to eradicate Ae. aegypti larvae by using natural larvicide. One of the plants that can be used as natural larvicides is avocado seeds (Persea americana Seed) which contain saponin. This study aims to determine the larvacidal activity of avocado seed extract sandgranules with LC50 of 8.87 mg.mL-1 against Ae. aegypti larvae. This study is an experimental research with a complete random design in a unidirectional pattern. The independent variable in this study is the variation concentration of Explotab as a disintegrant agent ie 2, 3, and 4%. Sand granules of avocado seed extract are made by wet granulation method. Results of the larvacidal activity test of avocado seed extract sand granules were analyzed by calculating the percentage of larvae mortality and statistical analysis using SPSS. The results of this study is the larvacidal activity of pure avocado seed extract with LC50 8.87 mg. L-1 is greater than the avocado seed extract sand granules. The addition of Explotab did not affect the total larvae mortality, but there was a significant difference in larvae mortality at 5 hours of sand granules exposure with explotab concentration of 3% and 4% (a significance value <0.05).